Women’s participation in violence management: A gender-based assessment - Akeem Aderayo Saraki; Agatha G. Chikelue (Indonesian Journal of Social Sciences, 2026)
Although conflict is not inevitable in human societies, violence is. Prevention and control of violence ought to consequently embrace integrative strategies, which incorporate various participants, including women. Nevertheless, the violence management systems in most societies, such as Nigeria, are still male-dominated. This paper will discuss the role of women in the management of violence in Ilorin metropolis, Kwara State, Nigeria, in terms of the level of their involvement, the obstacles to their involvement, and the ways they can contribute to peacebuilding efforts in the area. The research is based on the Gender Role Theory and takes the descriptive survey design with structured questionnaires that were distributed to the Ilorin East Local Government Area, Ilorin South Local Government Area, and Ilorin West Local Government Area residents. Purposive sampling was used to send out 100 questionnaires, and 80 valid responses (80%) were obtained. The results indicate that women are still underrepresented in violence management, even though they have the potential to provide useful mediation skills and networks in the community. The socio-cultural norms and institutional barriers hinder their participation. The paper concludes that community-based violence prevention and sustainable peace may be improved by enhancing the inclusion of women in communities by making them gender-sensitive and by building their capacity.